THE ROLE OF MATHEMATICS IN THE DEVELOPMENT OF STUDENTS' THINKING - Rakhmanov Istam Yarikulovich (European Science Publishing, 2023)
This article analyzes the concept of thinking and its components. Also, ways of forming and developing students' thinking and ways of mathematical education through teaching mathematics using special problems were considered.